D’une problématique locale-frontalière à un enjeu binational : le cas de la contrebande transfrontalière de carburants entre la Colombie et le Venezuela - Amanda Andrade Benitez (IdeAs)
This article analyzes the gradual inclusion of the illegal oil trade in the binational integration agenda between Venezuela and Colombia. Few scholars have focused on this question, which is generally examined through the prism of domestic –not foreign– policy. This study borrows from Cobb and Elders’ (1983) agenda setting theory and its development by Jones and Baumgartner (2005) on the evolution of political agendas following the incorporation of new issues. The purpose is to understand the ways in which illegal oil trade found its place in the bilateral energy integration agenda and became the subject of cooperation between Venezuela and Colombia. The economic effects of this illegal traffic along with its consequences on border security were crucial factors in the signing of a bilateral agreement. The energy agencies of Venezuela and Colombia were leading actors in this process and played a great role in the agenda setting process.